Ethnic competition in a divided America: The wall and the "Hispanic threat". (26th October 2021) - Serrano, Fernando; Schiavon, Jorge A.
Abstract: During his electoral campaign and while in office, President Donald Trump expressed his desire to build a wall along the US–Mexico border to control migration. Analyzing the conditions, circumstances, and demands of those Americans who want a wall with Mexico and Latin America is an imperative to understand better US–Latin American relations and ethnic competition not only during the Trump administration, but also in Joseph Biden's presidency. In this article, we argue, through quantitative analysis, that multiple factors, both individual and contextual, have a significant effect on the stance that US citizens have about immigration and the construction of the wall. Our study demonstrates that, in addition to sociodemographic variables, the distribution of the Hispanic population across the 50 US states generates a "Hispanic threat" which, as understood through ethnic competition theory, is a significant factor affecting Americans' views on the wall and immigration. Abstract : Durante su campaña electoral y una vez en el cargo, el presidente Donald Trump expresó su deseo de construir un muro a lo largo de la frontera entre México y Estados Unidos para controlar la migración. Analizar las condiciones, circunstancias y demandas de aquellos estadounidenses que quieren un muro con México y América Latina es un imperativo para entender mejor las relaciones diplomáticas y sociales entre Estados Unidos y América Latina, así como la competencia étnica en Estados Unidos, no sólo durante la administración Trump, sino también en la presidencia de Joseph Biden. En este artículo argumentamos, a través de un análisis cuantitativo, que múltiples factores, tanto individuales como contextuales, tienen un efecto significativo en la postura que los ciudadanos estadounidenses tienen sobre la inmigración y la construcción del muro. Asimismo, este estudio demuestra que, además de características sociodemográficas de los individuos, la distribución de la población hispana en los 50 estados de Estados Unidos genera un efecto que llamamos "la amenaza hispana", el cual analizado a través de la teoría de la competencia étnica es un factor significativo que afecta las preferencias de los estadounidenses frente al muro y la inmigración. Abstract : 美国总统唐纳德·特朗普在竞选和在位期间都曾表达了建立美国‐墨西哥边境墙以控制移民的愿望。为更好地理解特朗普政府和约瑟夫·拜登政府期间的美拉关系和族裔竞争，则必须分析一系列条件、情况、以及那些想与墨西哥和拉美建立边境墙的美国人的诉求。通过应用定量分析，我们主张，多个因素（包括个体因素和情境因素）对美国公民在移民和边境墙建立一事上的立场产生了显著影响。我们的研究证明，除了社会人口统计变量，美国50州的西班牙裔人口分布产生了一种"西班牙裔威胁"，在族裔竞争理论看来，这种威胁是影响美国人对边境墙和移民的看法的显著因素。